PERAN MEDIASI KINERJA KEUANGAN PADA HUBUNGAN DEWAN DIREKSI DENGAN REAKSI INVESTOR - Fransiskus Eduardus Daromes; Robert Jao (Jurnal Akuntansi, 2020)
The purpose of this study to investigate the effect of the executive board on the reaction of investors who are tested both directly and through financial performance. The population used is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) with a research period of 2015-2018. The number of samples is 32 companies every year which are selected by the method of purposive sampling and using secondary data from annual reports. The analytical method used is path analysis and mediation hypothesis testing is carried out using the Sobel test. Statistical testing results showed that the executive board has a positive and significant influence on financial performance, but not significant to investor reaction. Further financial performance has a positive and significant influence on investor reaction. This study also shows that financial performance plays a role in mediating the effect of the executive board on investor reaction.